Identification of heat resistance proteins and allergenic characterization in Mud Crab (Scylla paramamosain) - AbdulRaheem, Mustafa Nasrat (Tanjong Malim, 2019)
Identification of heat resistance proteins and allergenic characterization in Mud Crab (Scylla paramamosain) by AbdulRaheem, Mustafa Nasrat